PIRETROID PESTICIDES USE: KNOWLEDGE, ATTITUDE AND PRACTICE. (Fiep Bulletin - online, 2014)
Pyrethroids are synthetic insecticides of plant origin (Chrysanthemum Chrysanthemum and cinerariaefolium cocineum) that despite the low toxicity to humans is mainly through skin absorption and inhalation route becomes worrisome if the environment is closed. In the tables of intoxication observed nausea, vomiting, sore throat, abdominal pain, dizziness, fatigue, headaches, hyperexcitability, lack of coordination, and in severe cases coma and convulsions. Objectives: To assess consumer awareness about domestic pyrethroid pesticides, as well as precautions for use. Material and Methods: This was a descriptive, cross-sectional, quantitative, of which 100 people agreed be surveyed, answering a form containing objective questions that were used as variables. The data, once compiled, are presented in tables and simple frequency graphs expressed in numbers and percentages. The ethical aspects were respected, in accordance with Resolution No. 196/96 (CNS - MS). Results: It was observed that 62 % of the subjects use household insecticides, 90% not aware that household pesticides are from pyrethroid class, 78% only use insecticides to protect against insects and do not even know the deleterious effects on health; and only 22 % have associated symptoms and signs with poisoning by household insecticides. Conclusion: The results suggest that the subjects using pyrethroid insecticides, even without knowing what they are using, because this is the most used method in eliminating insects. However, the adverse effects are known, headaches and skin irritation are recognized as the most common, but few associate certain signs and symptoms such as poisoning from the use of this insecticide and do not read packaging during and after the purchase.
Keywords: Pyrethroids; insecticides; pesticides.